Leveraging the epistemic emotion of awe as a pedagogical tool to teach science. Issue 16 (2nd November 2022) - Gail Jones, M.; Nieuwsma, Julianna; Rende, K.; Carrier, Sarah; Refvem, Emma; Delgado, Cesar; Grifenhagen, Jill; Huff, Pamela
ABSTRACT: Awe is a complex emotion theorised to impact science learning and practice. In science education, awe has the potential to motivate explanation-seeking, promote conceptual change, and instill feelings of connectedness to the natural world. This exploratory study examined teachers' experiences with awe as well as their uses of awe in their science instruction. Thirty-four elementary (grades 4-5; n  =14) and middle school (grades 6-7; n  = 20) teachers completed a survey of awe perceptions and experiences and participated in a semi-structured interview. Results showed that science teachers report using awe-invoking classroom experiences in a variety of science disciplines with the intention of leveraging the emotional response in ways that facilitate learning outcomes and inspire long-term science interest. Teachers also reported numerous dispositional factors they perceived as being influential in governing awe experiences in science instruction including age, prior experiences, interest, curiosity, and the presence of co-occurring emotions. This study adds to the developing body of work around awe and science instruction, supports the findings from other fields related to the epistemic and self-transcendent nature of awe, and suggests that awe can be used to enhance science teaching and learning.